The phylogenetic analyses of anthriscus (Apiacea) species from Turkey based on Non-Coding trn regions of chloroplast genome - Sancar, P. Yilmaz; Tekin, M.; Civelek, S. (Wiley-Blackwell, 2016)
[Abstract Not Available]
41st FEBS Congress on Molecular and Systems Biology for a Better Life -- SEP 03-08, 2016 -- Kusadasi, TURKEY